2012
DOI: 10.1371/journal.pone.0035773
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Background Analysis of Protein C Deficiency Demonstrates a Recurrent Mutation Associated with Venous Thrombosis in Chinese Population

Abstract: BackgroundProtein C (PC) is one of the most important physiological inhibitors of coagulation proteases. Hereditary PC deficiency causes a predisposition to venous thrombosis (VT). The genetic characteristics of PC deficiency in the Chinese population remain unknown.MethodsThirty-four unrelated probands diagnosed with hereditary PC deficiency were investigated. PC activity and antigen levels were measured. Mutation analysis was performed by sequencing the PROC gene. In silico analyses, including PolyPhen-2, SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 49 publications
5
49
4
1
Order By: Relevance
“…In China, two recent studies found two predominant mutations of PROC, Lys173del and Arg189Trp, both in VTE patients and in the general population (Table 3). 32,33 In our study, Lys173del and Arg189Trp were observed in three and one patients, respectively, but not in the population group ( Figure 1A). Of note, all three patients with heterozygous Lys173del also had another PROC mutation (Table 2).…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Ncontrasting
confidence: 60%
“…In China, two recent studies found two predominant mutations of PROC, Lys173del and Arg189Trp, both in VTE patients and in the general population (Table 3). 32,33 In our study, Lys173del and Arg189Trp were observed in three and one patients, respectively, but not in the population group ( Figure 1A). Of note, all three patients with heterozygous Lys173del also had another PROC mutation (Table 2).…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Ncontrasting
confidence: 60%
“…34 The p. Cys64Tyr variant eliminates cysteine residues, which might result in aberrant protein multimerization or creation of the high -molecular--weight protein complex and impaired protein secretion. 33,35 A similar mutation in the same codon but with a different amino acid change (p.Cys64Gly) has been reported by Kuismanen et al 35 in a family from Finland, with a history of thrombosis and type I PC deficiency. The next new p.Cys175Arg variant within the PROC gene is located in the epidermal growth factor (EGF)-2 domain and might affect PC stability.…”
Section: Protein C Deficiencysupporting
confidence: 53%
“…These variants may potentially affect binding of the substrate. 33 Moreover, in the missense variant at position 387, cysteine is replaced by tyrosine, which may be important for disulfide bond formation, associated with protein stabilization. In turn, the p.Cys64Tyr variant of the PROC gene is located in the γ -carboxyglutamic domain within the PC structure.…”
Section: Protein C Deficiencymentioning
confidence: 99%
“…Several previous studies have revealed a relationship between DVT and genetic mutations in protein C, protein S, and antithrombin [24][25][26], which suggests that anticoagulant defects are the main cause of Asian thrombophilia. However, genetic polymorphisms of other natural anticoagulants did not attract enough attention.…”
Section: Discussionmentioning
confidence: 96%